Pendampingan Kegiatan Literasi Digital KKN Tema Budaya Digital di SMPS Kristen Kelurahan Onekore Kabupaten Ende - Nduru, Maria Purnama; Genua, Veronika (LPPM Universitas Flores, 2022)
The rapid development of information and communication technology demands readiness from its users. Debriefing and mentoring are things that need to be prepared and done, especially for students in schools. The purpose of this mentoring activity is so that students have knowledge and understanding of digital literacy so that they can use it safely, ethically and according to the culture of the Indonesian nation. The mentoring activity was carried out with lectures with the theme of digital culture and continued with question and answer. Lecture and Q&A activities took place smoothly and brought benefits to the participants. This activity is a useful activity and must still be continued programmatically in order to bring benefits. The areas of digital literacy including digital skills, ethical digitization and safe digitization still need to be given in the next school.